Effects of methylmercury on epigenetic markers in three model species: mink, chicken and yellow perch - Basu, Niladri (Comp Biochem Physiol C Toxicol Pharmacol, 2013)
We previously reported that methylmercury (MeHg) exposure is associated with DNA hypomethylation in the brain stem of male polar bears. Here, we conveniently use archived tissues obtained from controlled laboratory exposure studies to look for evidence that MeHg can disrupt DNA methylation across taxa. Brain (cerebrum) tissues from MeHg-exposed mink (Neovison vison), chicken (Gallus gallus) and yellow perch (Perca flavescens) were analyzed for total Hg levels and global DNA methylation. Tissues from chicken and mink, but not perch, were also analyzed for DNA methyltransferase (DNMT) activity. In mink we observed significant reductions in global DNA methylation in an environmentally-relevant dietary exposure group (1ppm MeHg), but not in a higher group (2ppm MeHg). DNMT activity was significantly reduced in all treatment groups. In chicken or yellow perch, no statistically significant effects of MeHg were observed. Dose-dependent trends were observed in the chicken data but the direction of the change was not consistent between the two endpoints. Our results suggest that MeHg can be epigenetically active in that it has the capacity to affect DNA methylation in mammals. The variability in results across species may suggest inter-taxa differences in epigenetic responses to MeHg, or may be related to differences among the exposure scenarios used as animals were exposed to MeHg through different routes (dietary, egg injection), for different periods of time (19 – 89 days) and at different life stages (embryonic, juvenile, adult).